Evaluation of a Direct PCR in Comparison with Routine Microscopy and In Vitro Culture for Diagnosis of Cutaneous Leishmaniasis - A Fazaeli; B Fuladi; M Hashemi Shahri; I Sharifi (Tehran University of Medical Sciences, 2007)
Background: Cutaneous leishmainasis (CL) is highly prevalent in several provinces of Iran, having been increased during the recent decade. The diagnosis of CL in most of clinical laboratories is usually performed using routine microscopy. However, this method is not sensitive enough, and the assessment and utilization of other methods, including a variety of PCR techniques, have been taken to consideration. Methods: In the present study, a direct PCR, based on kDNA primers, in comparison with the microscopic examination and in vitro NNN culture was evaluated for the detection of CL. The scrapings were taken from 73 patients from Mirjaveh, Sistan va Baluchestan province, and subjected to the comparative diagnoses. Results: The results showed that 38.4%, 55.5% and 60% of the specimens were positive by microscopy, PCR and NNN culture, respectively. Separate comparisons of both microscopy and PCR methods with NNN culture, showed that the sensitivity of the PCR (76%) is higher than that of microscopy (61%). The calculated specificity, however, was 100% for microscopy and 73% for PCR. The parasite species were also characterized by PCR. Conclusion: In addition to the higher sensitivity, this particular PCR, which uses species-specific primers, has a major advantage of identification of Leishmania species at the same time. It is, therefore, concluded that this PCR technique can be a suitable complement to the routine microscopic examination for diagnosis and identification of the parasite species from suspected leishmaniasis.